A kinematic and dynamic comparison of surface and underwater displacement in high level monofin swimming - Nicolas, G.; Bideau, B. (Human Movement Science, 2009)
Fin swimming performance can be divided into underwater and surface water races. World records are about 10% faster for underwater swimming vs. surface swimming, but little is known about the advantage of underwater swimming for monofin swimming. Some authors reported that the air-water interface influences the kinematics and leads to a narrow vertical amplitude of the fin. On the one hand, surface swimming is expected to affect drag parameters (cross-sectional area (S) and active drag (AD)) when compared to underwater swimming. On the other hand, the surface swimming technique may also affect efficiency (?F). The aim of this study is therefore to evaluate and compare drag parameters and efficiency during underwater and surface swimming. To this end, 12 international level monofin swimmers were measured during both underwater and surface swimming. Kinematic parameters (both dimensional and non-dimensional), ?F (calculated according to the Elongated-Body Theory), and AD (computed with Velocity Perturbation Method) were calculated for an underwater and a surface fin swimming trial, performed at maximal speed. As expected, results showed significantly lower velocities during surface swimming vs. underwater = 2.5 m s-1 vs. = 2.36 m s-1, p < .01). Velocities during underwater and surface swimming were strongly correlated (r = .97, p < .01). Underwater swimming was also associated with higher vertical amplitudes of the fin compared to surface swimming ( = 0.55 m vs. ) = 0.46 m, p < .01). Length-specific amplitudes (Aunder/Lb) were in the order of 20% during underwater swimming as for undulating fish, and significantly higher than during surface swimming (Asurf/Lb = 17%, p < .01). Efficiency for surface swimming was about 6% lower than for underwater swimming ( = 0.79 vs. = 0.74, p < .01). This decrease could be associated with an increase in swimming frequency for surface swimming ( = 2.15 Hz vs. = 2.08 Hz, p < .01). Active drag during surface swimming was about 7% higher than for underwater swimming ( = 78.9 N vs. = 84.7 N, p < .01). A significantly smaller cross-sectional area for surface swimming ( = 0.053 m2 vs. = 0.044 m2, p < .01) and higher drag coefficient for surface swimming ( = 0.47 vs. = 0.69, p < .01) were measured. Finally, correlation between cross-sectional area and vertical amplitude of the fin was reported for both underwater and surface swimming. These results suggest that the performance improvement during underwater swimming is not only linked to a wave drag reduction effect but also to a specific swimming technique due to the free surface.